Structuralists contra Serialists? Claude Lévi-Strauss and Pierre Boulez on Avant-Garde Music - Goldman, Jonathan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2010)
The adepts of serial music since the end of the 1950s seemed destined to ally themselves with structuralist thought—the broadly defined intellectual movement that profoundly marked the social sciences and humanities. The importance of the metaphor of language to the serialist project of Pierre Boulez in particular seemed sufficient to pave the way towards a conceptual alliance between avant-garde music and structuralist thought. Nevertheless, Claude Lévi-Strauss’s acerbic pronouncements on serial music as well as musique concrète that appeared in the famous “Overture” to The Raw and the Cooked (1964) made it clear that Lévi-Strauss was no friend of the serialist project. Drawing on recent research by Jean-Jacques Nattiez, Nicolas Donin, and Frédéric Keck, this article will argue that the serialist compositional project of the postwar era, embodied primarily in the figure of Pierre Boulez, can be considered “structuralist” in the sense of the intellectual movement promulgated by Claude Lévi-Strauss, despite the latter’s denunciation of serial music.